Peran budaya sekolah dalam pembentukan karakter sosial siswa sekolah dasar - Nurlia Ari Dwiyanti; Heri Maria Zulfiati; Dwi Wijayanti (Trihayu: Jurnal Pendidikan Ke-SD-an, 2026)
School culture constitutes an important educational environment for internalizing social values through habituation, role modeling, and everyday social interactions. This study aimed to analyze the role of school culture in developing students' social character, identify the supporting and inhibiting factors affecting its implementation, and describe the school's efforts to address challenges in social character development at SD Negeri Minggiran, Yogyakarta City. The study employed a qualitative approach with a case study design. The participants comprised the principal, teachers, and students selected purposively. Data were collected through observations, interviews, and documentation and analyzed using the interactive model of Miles, Huberman, and Saldaña. Data trustworthiness was strengthened through source, technique, and time triangulation. The findings showed that school culture contributed to the development of discipline, responsibility, empathy, cooperation, mutual assistance (gotong royong), and politeness through the 5S+1J habituation, morning assemblies, congregational prayers, charitable activities, literacy programs, environmental cleanliness, and other social activities. A distinctive finding was the integration of local wisdom through the use of the Javanese greeting sugeng enjang, the Javanese language, and unggah-ungguh or Javanese etiquette in everyday interactions. Supporting factors included teacher role modeling, consistent habituation, stakeholder involvement, parent-school collaboration, and adequate facilities. The main barriers were differences in students' backgrounds and inconsistent character reinforcement within families. The school addressed these challenges by strengthening habituation programs, providing individual guidance, reinforcing teacher role modeling, and maintaining continuous communication and collaboration with parents. These findings emphasize the importance of consistent school culture and continuity between school- and family-based character education in developing elementary students' social character.